Kunst, natuur en biotoop; nature morte ? - Pas, J. (Gent : Ludion, 1995)
Bernier, Pascal ; van Biesen, Stefaan ; Bisschop, Geert ; Casaer, Paul ; de Cordier, Thierry ; Crabeels, Cel ; Deleu, Luc ; Denmark ; Donker, Dick ; Dossche, Caroline ; Duchateau, Hugo ; Efrat, Benni ; Fastenaekens, Gilbert ; Jodogne, Lucas ; Kempenaers, Jan ; Körmeling, John ; Lemmen, Hans ; Lybeer, Leen ; Massart, Jean-Georges ; Moszowski, Wladimir ; Oosterlynck, Baudouin ; Perneel, Paul ; De Roover, Marc ; De Smet, Yves ; Vanhemelryck, Kris ; Verschueren, Bob ; Visser, Jan Eric ; Vos, Jan ; Wastijn & Deschuymer ; De Wit, Johan
boek